Legal remedies in asylum and immigration law - Králová, Alžbeta (Central European Public Administration Review, 2018)
The paper tackles a widely discussed but still rather under-researched area of asylum and immigration law, more precisely its procedural aspects and its interactions within the public administration and administrative judiciary. It contributes to the debate about the Europeanization of public administration within the specific context of asylum and immigration law. The purpose of the paper is to examine the influence of European Union law on the legal regulation of administrative and judicial review of decisions rendered in asylum and immigration procedures. The research is based on an in-depth analysis of the dynamics of amendments and the motivation of national legislation while adopting new procedural rules in the above-mentioned areas on the case of the Czech Republic (based on the description and analysis of the legal regulation, explanatory memoranda and the case law, supplemented with certain comparative aspects). The procedural autonomy principle gets increasingly limited by other principles, namely the effectiveness principle and the principle of effective judicial protection. The paper therefore focuses on the margin of appreciation left to the national legislator: it determines whether the principle of procedural autonomy keeps the real relevancy while harmonising the asylum and immigration law and what is the influence of tensions between the aforementioned principles. The research shows that the legislator still maintains quite a wide degree of margin of appreciation in the administrative and judicial review of asylum and immigration decisions (apart from the visa procedures). However, a broadening of the interpretation of the effective judicial protection principle as provided by Article 47 of the Charter of Fundamental Rights of the EU decreases the scope of procedural autonomy and has the potential to influence not only individual legal remedy, but also the system of administrative or judicial remedies as such. Besides the overall findings related to the influence of European Union law on the review in asylum and immigration procedures, the article tackles numerous practical implications of amendments based in European Union law and practical challenges for the administrative and judicial review in concerned area of law. The paper provides a reaction to tensions coming from the need to find the balance between the obligation to provide an effective remedy and between the autonomy of Member States and their attempts to preserve national procedural traditions and specificities within the system of administrative and judicial review. It is original by its overall view on the problematic of remedies in asylum and immigration law and by a new perspective of interactions between national legislation and European Union law. Although the research is limited to the case study of the Czech Republic, certain aspects apply to other Member States with similarities within their system of administrative and judicial review.
Keywords: azil; Evropska unija; migracije; pravna sredstva; procesna avtonomija